(untitled) (Journal of Dhaka National Medical College & Hospital, 2018)
Osteoporosis is an important public health problem leading to an increased risk of spontaneous and traumatic fracture. Osteoporosis is a condition of fragile bone disease and decrease in bone mass density. It occurs mostly after the age of 35 years, bone loss is more in women after menopause. In most cases patient have no symptoms until bone fracture occurs. The diagnosis of osteoporosis can be suggestive by X-ray and confirmed by measuring bone mass density (BMD). There are some effective treatments of osteoporosis but in addition to that stopping of alcohol abuse, smoking and assuring adequate level of calcium and vitamin D is the target to prevent this silent killer disease. J. Dhaka National Med. Coll. Hos. 2018; 24 (02): 54-56